(untitled) (African Journal of Biomedical Research, 2023)
The important of quality stain for proper diagnosis of haemoparasites cannot be overemphasized in parasitology. Natural stains are safer and more eco-friendly than synthetic ones. Henna leaves methanolic extract solution was optimized and used alongside Giemsia and Romanowsky stains to study prevalence of canine ehrlichiosis in Makurdi. Henna leaves methanol extract solution was optimized, 10% for 45 minutes stain was used independently alongside Giemsia and Romanowsky stains to study prevalence of Ehrlichia canis in dogs. One hundred dogs of three different breeds were sampled from four different locations within Makurdi and examined under microscope. The study revealed that henna is not a good stain for haemoparasites since it cannot be picked by the surface glycoprotein of the cell membrane of the parasites. Romanowsky stain revealed 3% prevalence while others recorded zero prevalence. Adult, male and exotic breed of dogs recorded higher prevalence than young, female and other breeds of dogs. The prevalence recorded agreed with the previous reports from western Nigeria but was at variance with reports from other part of the world. Low sensitivity of the method used and the stages of the disease may be possible reasons for low prevalence observed in the study. Henna is not recommended as a good stain for diagnosis of haemoparasites. Breed and age are predisposing factors to the disease, but sex has no significant association with the disease. A more sensitive method and different period of the year should be used for future similar study.